Knowledge-Attitudes-Practices about Malaria among Communities in Southern Benin - Germain Gil Padonou; Judith G. Gbenoudon; Razaki Osse; Albert Salako; Casimir Kpanou; Herman Sagbohan; Virgile Gnanguenon; Frederick Oke Agbo; Olivier Oussou; Martin Codjo Akogbeto (Intelektual Pustaka Media Utama, 2018)
Malaria still remains the main public health problem in Benin. We explored the determinants that influenced malaria treatment as well as protective behaviors, to generate a framework of useful ideas as alternative strategies against malaria. A cross-sectional survey of the knowledge, attitudes and practices (KAP) was conducted at Hozin, Vakon and Agblangandan districts in southern region of Benin. Descriptive statistics were computed and mixed logistic regression helped evaluating the relationship between frequency of each category of severity of malaria and sex group, educational level, treatment, means of self-protection against mosquitoes and identification of the cause of malaria. A significant proportion 750 (81.3%) (p<0.001) of participants stated that malaria was caused by mosquitoes. The respondents who mentioned sun as the cause of malaria, have trivialized more malaria in a proportion of about 59.30% (OR=2.67 [95% CI 1.61-4.44]) followed by those who have reported the cause of body weakness (43.68%) (OR=2.97 [95% CI 1.68-5.28]). Poor knowledge justifies the trivialization of the disease and poor management of malaria control means. National Malaria Control Programs should improve access to education, especially for women and could help improving prevention and control behaviours against malaria in communities.